2020
DOI: 10.1007/s00705-020-04562-1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the mechanism of anti-herpes action of two novel semisynthetic cardenolide derivatives

Abstract: Human herpesviruses are among the most prevalent pathogens worldwide and have become an important public health issue. Recurrent infections and the emergence of resistant viral strains reinforce the need of searching new drugs to treat herpes virus infections. Cardiac glycosides are used clinically to treat cardiovascular disturbances, such as congestive heart failure and atrial arrhythmias. In recent years, they have sparked new interest in their potential anti-herpes action. It has been previously reported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 83 publications
0
15
0
Order By: Relevance
“…Cardenolides are molecules clinically used to treat heart diseases, such as heart failure, arrhythmias, and cardiogenic shock [ 25 , 26 , 27 ]. However, several studies have suggested promising effects for the treatment of other diseases [ 54 ], including those caused by viral infections [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Even though CGs have been investigated against many viruses, little is known about their potential anti-influenza activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardenolides are molecules clinically used to treat heart diseases, such as heart failure, arrhythmias, and cardiogenic shock [ 25 , 26 , 27 ]. However, several studies have suggested promising effects for the treatment of other diseases [ 54 ], including those caused by viral infections [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Even though CGs have been investigated against many viruses, little is known about their potential anti-influenza activity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, these compounds have been investigated for the treatment of other pathological conditions, such as viral infections. Their potential antiviral activity against a wide variety of viruses has been reported, such as adenovirus [ 29 ], chikungunya virus [ 30 ], coronavirus [ 31 , 32 , 33 ], cytomegalovirus [ 34 , 35 , 36 ], dengue virus [ 37 ], herpes virus [ 38 , 39 , 40 , 41 ], HIV [ 42 , 43 , 44 ], human papillomavirus [ 45 ], influenza virus [ 46 , 47 , 48 ], and respiratory syncytial virus [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the attribute of HDF to intrupt protein expression of HSV-1, western blotting technique was employed. 24,25) Vero cells, previously washed with phosphate buffer saline centrifuged for 15 minutes and pellets were adjourned in cold lymph buffer solution containing 10mM phenyl methacophenol fluoride phosphatase as inhibitor mixture along with 2% triton solution, incubated for 30 minutes at 0°C temperature and supernatants were arrassed to negotiate protein expression. The protein contents were aloofed by gel electrophoresis technique in 10% S.D.S.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…They also presented data demonstrating that this cardiac glycoside was effective against acyclovir-resistant viruses. Recently, Boff et al 78 published their experience with several semisynthetic cardenolides, C10 (3β-[(N-(2-hydroxyethyl) aminoacetyl]amino-3-deoxydigitoxigenin)) and C11 (3β-(hydroxyacetyl) amino-3-deoxydigitoxigenin), both of which inhibited HSV-1 and HSV-2 at nM concentrations. Both compounds inhibited the intermediate and final steps of HSV replication, but not the earlier stages, based on the complete reduction in the expression of UL42 (β) and gD (γ) proteins and partial reduction of ICP27 (α).…”
Section: Introductionmentioning
confidence: 99%